e-Announcement: Aplikasi Sistem Informasi Pengumuman Sekolah - M. Syahid Nur Wahid; Anggun Sakila; Ilyas Febrian Rahmat; Reza Elka Ferani; Andi Ariq Naufal Fahza (Indonesian Technology and Education Journal, 2024)
Announcement and communication apps have gained popularity as a way to make it easier for parents, teachers and students to communicate with schools. This article discusses making APKs that aim to increase the effectiveness and efficiency of school management. Data collection techniques include literature study. The waterfall method is used for data analysis. The results of this study indicate that Apk development can increase the effectiveness of communication in the school environment, increase information accessibility, and facilitate information management. In addition, the message feature in this application allows teachers and parents to communicate directly